Error‐related electromyographic activity over the corrugator supercilii is associated with neural performance monitoring. (16th October 2015) - Elkins‐Brown, Nathaniel; Saunders, Blair; Inzlicht, Michael
Abstract: Emerging research in social and affective neuroscience has implicated a role for affect and motivation in performance monitoring and cognitive control. No study, however, has investigated whether facial electromyography (EMG) over the corrugator supercilii—a measure associated with negative affect and the exertion of effort—is related to neural performance monitoring. Here, we explored these potential relationships by simultaneously measuring the error‐related negativity, error positivity (Pe), and facial EMG over the corrugator supercilii muscle during a punished, inhibitory control task. We found evidence for increased facial EMG activity over the corrugator immediately following error responses, and this activity was related to the Pe for both between‐ and within‐subject analyses. These results are consistent with the idea that early, avoidance‐motivated processes are associated with performance monitoring, and that such processes may also be related to orienting toward errors, the emergence of error awareness, or both.